A Critical Review on “ Alnahvo Alasasi” Book - Vesal Maymandi; Samira Sedighi Mournani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Grammar and syntax is one of the branches of linguistics which was created with the motivation of correct application and usage of Arabic language specially Qoran language and was led to the appearance of numerous schools and works in this science. One of the contemporary books which has been written in the field of Arabic language teaching is “Alnahvo Alasasi” that was compiled by three Kuwaitian researchers  who have written a mediocre limit with a different style in grammar and syntax. In this research, it was attempted to use an analytical-descriptive approach in order to criticize the sources and texts of Arabic teaching. The present paper aims to introduce the book and analyze    its different sections such as  apparent structure,form, and contents including definitions, problem statement, evidence, exercises, and sources of book. In addition, it aims to bring to the fore not only the advantages of the book such as having a consistent and uniform manner to state some various topics, using simple and fluent texts and diversity in exercises as much as possible, but also the shortcomings such as removing or incomplete expression of some essential issues the lack of observance of principle in simple to difficult arrangement of the exercises, and lack of sources.